Peran Dimensi Assurance Dalam Membentuk Kepuasan Mahasiswa Terhadap Layanan Administrasi Akademik (Studi Kasus Pada Politeknik Pariwisata Palembang) - Herdianto, Herdianto; Suandi, Suandi; juliartha, Edwar; Fanada, Mery; Nazaputra Kiemas, Muhammad Giri Ramanda (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2026)
The Assurance dimension in the SERVQUAL model serves as the foundation for building student trust in the quality of higher education academic administrative services. This study aims to deeply analyze the role of the Assurance dimension in shaping student satisfaction at Palembang Tourism Polytechnic (Poltekpar Palembang), encompassing: per-indicator satisfaction levels, cross-cohort satisfaction patterns, service gap analysis, and implications for student loyalty and institutional quality. Using descriptive quantitative methods with 93 respondents from 1,245 active students selected via proportionate stratified random sampling, the study employed a 4-point Likert scale instrument adapted from the SERVQUAL model. Results show the Assurance dimension achieved 73% satisfaction, ranking second highest among five SERVQUAL dimensions, yet leaving a 27% dissatisfaction gap. Staff accountability in handling service re-delivery (75%) emerged as the primary strength, while direct on-demand service fulfillment (70%) constitutes the critical weakness. Cross-cohort analysis reveals an inverted-U pattern: the 2022 cohort scored highest (74.4%) while the 2021 cohort scored lowest (71.5%), interpreted as reflecting differences in service interaction intensity and expectation formation. Gap analysis identifies three root sources: inconsistent staff competence, absence of published SOPs, and limited service information systems. The study concludes that improving Assurance requires three-layer intervention: human resource competency strengthening, SOP-based service reform, and development of a service excellence culture grounded in institutional trust.